2011
DOI: 10.1111/j.1467-8624.2011.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Practicing 4 = 2 + 2: Nontraditional Problem Formats Facilitate Children’s Understanding of Mathematical Equivalence

Abstract: This study examined whether practice with arithmetic problems presented in a nontraditional problem format improves understanding of mathematical equivalence. Children (M age = 8;0; N = 90) were randomly assigned to practice addition in one of three conditions: (a) traditional, in which problems were presented in the traditional "operations on left side" format (e.g., 9 + 8 = 17); (b) nontraditional, in which problems were presented in a nontraditional format (e.g., 17 = 9 + 8); or (c) no extra practice. Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 63 publications
9
87
1
Order By: Relevance
“…Results from this study suggest that any classroom time devoted to improving students' conceptual understanding of the equals sign is likely well spent; fortunately, a variety of tools, materials, and instructional suggestions are already available for this purpose, including utilizing a balance scale (Vlassis, 2002) or introducing arithmetic sentences that are in unconventional forms, such as 7 = 2 + 5, etc. (McNeil, Fyfe, Petersen, Dunwiddie, & Brletic-Shipley, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study suggest that any classroom time devoted to improving students' conceptual understanding of the equals sign is likely well spent; fortunately, a variety of tools, materials, and instructional suggestions are already available for this purpose, including utilizing a balance scale (Vlassis, 2002) or introducing arithmetic sentences that are in unconventional forms, such as 7 = 2 + 5, etc. (McNeil, Fyfe, Petersen, Dunwiddie, & Brletic-Shipley, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As they move through secondary school many children gradually develop a sameness-relational conception of the equals sign in which "=" is seen as meaning "is the same as" and a wide variety of statement types are accepted McNeil et al 2011;Rittle-Johnson et al 2011). …”
Section: Children's Conceptions Of the Equals Signmentioning
confidence: 99%
“…Much research has investigated how children move from an operational understanding of the equals sign in their early years of schooling to a more relational understanding in later years (Baroody and Ginsburg 1983;Behr, Erlwanger and Nichols 1976;Denmark, Barco and Voran 1976;Kieran 1981;McNeil 2008;McNeil et al 2011;Rittle-Johnson et al 2011). Jones and Pratt (2012) argued that research to date has operationalised the relational understanding of the equals sign exclusively in terms of sameness.…”
Section: Introductionmentioning
confidence: 99%
“…However the traditional curriculum did not better prepare children for solving equations despite including substantially more equation solving practice. Analogously, McNeil et al (2011) found that emphasising a computational view of arithmetic equations hampered young children's relational understanding, but emphasising a relational view did not hamper computational proficiency. Nevertheless, even when learners display a conceptual understanding of algebra development is unlikely to be straightforward.…”
mentioning
confidence: 93%
“…This is a disappointment in light of the research team's impressive contribution to theory on the development of algebraic concepts elsewhere (e.g. McNeil et al, 2011). Conversely, many chapters are explicitly theory-based, and many authors exemplify their theoretical approach with excerpts from curricula, resources, classroom episodes and interview transcripts.…”
mentioning
confidence: 99%